Teratogenic Effect of Levetiracetam Drug on the Development of the Kidney in Embryo Rat - Al-Ibrahimi, Lamyaa H. M.; Al-Bakri, Nahla A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The new antiepileptic drugs, levetiracetam (LEV), are used to treat tonic-clonic seizures and myoclonic seizures in adults and children. Thirty pregnant rats were enrolled, which were divided into two groups A control (10), B treated (20). Group (A) were given distilled water orally for 15 days of pregnancy period. The other group was subdivided into two subgroups B1, B2 (each with 10 rats), which were treated with LEV for 14 days for subgroup (B1) and 15 days for the other subgroup (B2). The drug (350 mg/kg/day) is administered orally. Based on our results there was damage in the kidney due to the toxicity of the drug. The histopathological effects is represented by damage of cortical glomeruli in which there were hemorrhage, shrinking, accumulation of glomerular cells, and enlargement of capsular space. Severe malformations in the kidney were observed when the drug is used constantly during the organogenesis stages of pregnancy.